2013
DOI: 10.1186/1480-9222-15-5
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of DNA affects the accuracy of the DNA quantitation by the commonly used methods

Abstract: BackgroundSpecific applications and modern technologies, like non-invasive prenatal testing, non-invasive cancer diagnostic and next generation sequencing, are currently in the focus of researchers worldwide. These have common characteristics in use of highly fragmented DNA molecules for analysis. Hence, for the performance of molecular methods, DNA concentration is a crucial parameter; we compared the influence of different levels of DNA fragmentation on the accuracy of DNA concentration measurements.ResultsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 22 publications
(37 reference statements)
3
63
2
4
Order By: Relevance
“…It is reasonable to assume that the DNA extracted by QIA was purified by binding to the silica membrane, whereas the DNA extracted by WAX included more contaminants, such as proteins, due to total tissue extraction. PicoGreen dye is not affected by contaminants, however it is affected by DNA integrity (19)(20)(21). In the present study, it was demonstrated that the DNA extracted by WAX was more fragmented than that extracted by QIA.…”
Section: Discussionmentioning
confidence: 55%
“…It is reasonable to assume that the DNA extracted by QIA was purified by binding to the silica membrane, whereas the DNA extracted by WAX included more contaminants, such as proteins, due to total tissue extraction. PicoGreen dye is not affected by contaminants, however it is affected by DNA integrity (19)(20)(21). In the present study, it was demonstrated that the DNA extracted by WAX was more fragmented than that extracted by QIA.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless prior to massively parallel sequencing fluorescent dye-based quantification methods are commonly used as they are considered to be the easiest, most reliable and cost effective methods [3]. From our point of view qPCR is the least feasible method as it is time consuming, expensive and not practicable in routine laboratories with a high sample throughput, which is also stated by other studies [13], [15]. Additionally, our study showed that samples with a low amount of amplifiable DNA, determined by qPCR, could still be amplified by a well-established PCR and the DNA sample could still be used for mutation detection.…”
Section: Resultsmentioning
confidence: 91%
“…SYBR Green) or 5′ hydrolysis probes (e.g. Taqman ® ) coupled with real-time quantitative PCR (qPCR) (Robin et al 2016;Sedlackova et al 2013). Further evaluation of the results obtained in this study could be attempted in the future with the use of more sensitive methods as accurate measurement of DNA concentration can be especially crucial for downstream analysis of the DNA sample, especially for next generation sequencing (NGS) or high throughput genotyping studies.…”
Section: Discussionmentioning
confidence: 96%